PHYSICAL CHARACTERISTICS TEST OF FAKE RICE COMPOSTING WITH TARO AND ONGGOK FLOURS - Dinarki, Anis - (The University of Lampung, 2014)
Analog rice is made of non paddy flour. The utilization of taro flour as material for analog rice needs to be developed. The purpose of this study was to measure the characteristics of analog rice made from taro flour and onggok flour such as uniformity of grain, bulk density, moisture content, water absorption, and extention ability. Granulation of the analog rice was done using a granulator with 6 different compositions of taro flour-coarse cassava flour, and taro flour – fine cassava flour with ratio of 75:25 , 85:15 , 95:5, respectively. The results showed that the diameter of grain of analog rice affect uniformity, moisture content, water absorption, and extention ability. In mixture of taro flour and coarse cassava flour yielded diameter of 2-4.70 mm, bulk density of 0.77-0.84 g/cm3, the water content of 11.84-12.85 %, 62.15-94.25 % water absorption, 9.30-13.46 % extention ability, whereas the mixture of cassava flour and taro flour produced diameter > 4.70, bulk density 0.74-0.83 g/cm3, the water content of 10.76-13.31 %, 57.03-76.94 % water absorption, 11.33-12:53 % extention ability. Starch content of material affect the water absorption and extention ability of the analog rice.Keywords : Taro, taro flour, onggok flour, rice, analog rice.